MOLECULAR DOCKING AND IN SILICO ANALYSIS OF PSIDIUM GUAJAVA L. LEAF METABOLITES AGAINST PfDHFR AND PfLDH: UNVEILING NEW ANTIMALARIAL CANDIDATES - Nurcahyo Iman Prakoso; Apriyadi Pramana; Alyaa Natta Cherry Waluyo; Gani Purwiandono; Pinus Jumaryatno; Atina Ahdika (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2026)
Resistance of Plasmodium falciparum to conventional antimalarial drugs has created an urgent need for new drug candidates. In this study, six bioactive compounds identified from guava (Psidium guajava L.) leaves, namely quercetin, guaijaverin, 3-tert-butyl-4-methoxyphenol, petasitolone, hyptatic acid, and stigmastane-3,6-dione, were evaluated as potential inhibitors of PfDHFR and PfLDH using in silico approaches, including target identification and validation, molecular docking, binding pocket analysis, and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) prediction. Both enzymes were highly expressed during the ring stage, essential, non-redundant, and selective toward human homologs, supporting their suitability as antimalarial targets. Molecular docking against PfDHFR revealed that stigmastane-3,6-dione exhibited the strongest binding affinity (−10.4 kcal/mol), followed by guaijaverin (−9.6 kcal/mol) and quercetin (−8.7 kcal/mol), with stable interactions involving key active-site residues. Against PfLDH, quercetin and hyptatic acid showed the best binding affinity (−8.0 kcal/mol), followed by guaijaverin and stigmastane-3,6-dione (−7.7 kcal/mol). However, binding pocket analysis showed that only quercetin, guaijaverin, and petasitolone properly occupied the active binding pocket, whereas hyptatic acid and stigmastane-3,6-dione interacted outside the catalytic site. These findings indicate that quercetin, guaijaverin, and petasitolone may act through competitive inhibition. Molecular dynamics simulation (20 ns) was subsequently performed on selected protein–ligand complexes, in which quercetin and stigmastane-3,6-dione were selected as representative top ligands, while chloroquine was included as a positive control. RMSD, RMSF, and ligand movement analyses demonstrated that quercetin exhibited greater stability in PfLDH than chloroquine. Overall, this study identifies quercetin, guaijaverin, petasitolone, and stigmastane-3,6-dione as promising antimalarial candidates, supported by ADMET predictions showing favorable pharmacokinetic properties and providing a strong rationale for further in vitro and in vivo evaluation.